To simplify the expression \( 2 \cdot (3 + 3d) \), you can distribute the 2:
\[ 2 \cdot (3 + 3d) = 2 \cdot 3 + 2 \cdot 3d = 6 + 6d \]
So, the simplified expression is:
\[ 6 + 6d \]
11 answers
To simplify the expression \( 2 \cdot (3 + 3d) \), you can distribute the 2:
\[ 2 \cdot (3 + 3d) = 2 \cdot 3 + 2 \cdot 3d = 6 + 6d \]
So, the simplified expression is:
\[ 6 + 6d \]
To simplify the expression \( 2 \cdot (2 + 3d) \), you can distribute the 2:
\[ 2 \cdot (2 + 3d) = 2 \cdot 2 + 2 \cdot 3d = 4 + 6d \]
So, the simplified expression is:
\[ 4 + 6d \]
To simplify the expression \( 4 \cdot (5 + 4d) \), you can distribute the 4:
\[ 4 \cdot (5 + 4d) = 4 \cdot 5 + 4 \cdot 4d = 20 + 16d \]
So, the simplified expression is:
\[ 20 + 16d \]
To calculate \(2 \cdot \frac{3}{2}\), you can multiply the whole number by the fraction:
\[ 2 \cdot \frac{3}{2} = \frac{2 \cdot 3}{2} = \frac{6}{2} = 3 \]
So, \(2 \cdot \frac{3}{2} = 3\).
To simplify the expression \( 2 \cdot (2 + 2m) \), you can distribute the 2:
\[ 2 \cdot (2 + 2m) = 2 \cdot 2 + 2 \cdot 2m = 4 + 4m \]
So, the simplified expression is:
\[ 4 + 4m \]
To simplify the expression \( 3(5 + 2m) \), you can distribute the 3:
\[ 3(5 + 2m) = 3 \cdot 5 + 3 \cdot 2m = 15 + 6m \]
So, the simplified expression is:
\[ 15 + 6m \]